Trust, privacy and security in digital business 8th International Conference, TrustBus 2011, Toulouse, France, August 29 - September 2, 2011. Proceedings - TrustBus (Conference) Toulouse, France) 2011; Furnell, Steven 1970-; Lambrinoudakis, Costas; Pernul, Günther 1961-; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
This book constitutes the refereed proceedings of the 8th International Conference on Trust and Privacy in Digital Business, TrustBus 2011, held in Toulouse, France, in August/September 2011 in conjunction with DEXA 2011. The 18 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in the following topical sections: identity and trust management; security and privacy models for pervasive information systems; reliability and security of content and data; authentication and authorization in digital business; intrusion detection and information filtering; management of privacy and confidentiality; and cryptographic protocols/usability of security.
Electronic reproduction.
Keywords: Electronic commerce -- Security measures -- Congresses; Internet -- Security measures -- Congresses; Computer networks -- Security measures -- Congresses; Electronic books